A cobra na cosmologia das rezadeiras amazônicas = The snake in the cosmology of the Amazonian mourners - Silva, Jerônimo da Silva e (Ciencias sociales y religión, 2020)
In order to present the significance and meaning of the existence of the snake in Amazonian communities' lives, we must understand this like a cosmological manifestation of enchanted people and entities of Afro-Brazilian indigenous beliefs; this brings the dialogue with oral narratives of healers at Zona Bragantina, northeast of Pará. Through readings in Social Anthropology and methodological orientation of Oral History, the role given to the ophidian as a constituent element of the perception of healing practices is apprehended. The narratives evoke visions, ecstasies, possessions, and various omens that denote these women’s beliefs and their contacts with the “snake charmer”, exposing cultural singularities in this area of the Brazilian Amazon.